The Application of Hebel Incinerators as a Waste Management Solution in Sindangpalay Village - M. Alka Maulana; Siti Barokah; Adisti Puspita Rahayu; Widi Febrianti Rahayu; Muhamad Fajarudin; Resha Artharegina; Lukman Hakim; Dani Fajar Purnama; Fithri Suciati; Sobali Suswandy (Siber Nusantara Research, 2026)
The issue of household waste management remains an environmental challenge due to the increasing volume of waste generated and the continued practice of open burning, which has the potential to cause air pollution and public health hazards. This community service initiative aims to implement an aerated concrete incinerator as an alternative solution for more effective, economical, and sustainable household waste management in Sindangpalay Village. The activity was carried out using a Participatory Action Research (PAR) approach, actively involving the community in every stage of the process—from problem identification, program planning, and implementation to monitoring and evaluation. This included field observations, environmental outreach and education, participatory construction of the incinerators, training on equipment use, and the implementation of waste management using lightweight concrete incinerators. The results of the activity showed that the use of lightweight concrete incinerators helped reduce the volume of household waste, curbed open burning practices, and increased community awareness and participation in more environmentally friendly waste management. In addition, this participatory approach helps encourage changes in community behavior regarding waste sorting and the simple application of the 3R principles (Reduce, Reuse, Recycle), making the use of lightweight concrete incinerators an effective tool for supporting sustainable community-based waste management.